2017
DOI: 10.1371/journal.pone.0184806
|View full text |Cite
|
Sign up to set email alerts
|

What does the media say about palliative care? A descriptive study of news coverage in written media in Spain

Abstract: IntroductionThe goal of palliative care (PC) is to improve the quality of life of terminal stage patients and their families. The subject frequently appears in the mass-media and this helps create a socially accepted identity. The aim of this study is to describe and analyse PC related news items appeared in the Spanish written media.MethodologyA descriptive cross-sectional study was designed. Considering diffusion, scope and the range in editorial policy criteria, four printed newspapers (PN) were selected, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…Our analysis found that print media references were mainly related to current socio-political debates in the immediate present regarding proposed end-of-life legislation and controversial legal cases. Politicians and health professionals were the main actors providing messages on PC, with politicians lending an ideological political or moral slant to their discourse, and health professionals framing theirs through educational information, which is consistent with the results of a quantitative study of news coverage related to PC in written media (printed and digital) in Spain [23]. Although the political and moral discourses at times referenced the benefits of PC, these messages were entangled in ideological debates and controversies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our analysis found that print media references were mainly related to current socio-political debates in the immediate present regarding proposed end-of-life legislation and controversial legal cases. Politicians and health professionals were the main actors providing messages on PC, with politicians lending an ideological political or moral slant to their discourse, and health professionals framing theirs through educational information, which is consistent with the results of a quantitative study of news coverage related to PC in written media (printed and digital) in Spain [23]. Although the political and moral discourses at times referenced the benefits of PC, these messages were entangled in ideological debates and controversies.…”
Section: Discussionsupporting
confidence: 73%
“…A total of 295 news items were identified containing the terms searched, and after eliminating duplicate news items and those in which the terms were not correctly identified, 262 articles were included in the study: 135 in ABC , 65 in El País , 24 in El Mundo and 38 in La Vanguardia (S1 File). A quantitative description of the news items identified can be found in an earlier article showing that most of the news items were published in the newspapers’ ‘Culture and Society’ (38%) and ‘National’ sections (30%), followed by ‘Editorial’ and ‘Reader’s letters’ (19%) and other sections (12%), with only two per cent appearing in the ‘Health’ section [23]. Due to this variability, the diversity of the language, how it was structured and the graphics resources used was conditioned by the type and scope of each article.…”
Section: Resultsmentioning
confidence: 99%
“…This study as far as we know is the only one that studies the messages that PC professionals relay to patients and caregivers during their clinical encounters. It identifies three main messages that have little in common with the messages that are transmitted in the media according to other studies [6,18]. "We are a team focused on your wellbeing" is a clear message transmitted by health professionals explaining "what they do" rather than "who they are".…”
Section: Discussionmentioning
confidence: 99%
“…A misunderstanding of PC persists among the general public, healthcare professionals and policy makers, revealing the problem of knowledge transfer that adequately reflects reality [6,7]. A study that analysed 600 articles from Spanish newspapers concluded that the information regarding PC does not accurately reflect clinical practice and its nature.…”
mentioning
confidence: 99%
See 1 more Smart Citation